Familial Hemiplegic Migraine With Asymmetric Encephalopathy Secondary to ATP1A2 Mutation: A Case Series. Issue 1 (January 2018) - Murphy, Olwen C.; Merwick, Aine; O'Mahony, Olivia; Ryan, Aisling M.; McNamara, Brian
Abstract : Introduction: Familial hemiplegic migraine (FHM) is a genetic disease with a variable clinical phenotype. The imaging and electroencephalogram (EEG) correlates of FHM are not well described. Case Series: We describe a case series of five young women aged 12 to 32 years. Each case presented with headache, encephalopathy, and hemiparesis of varying severity. One patient developed seizures. All patients improved spontaneously. Investigations: Asymmetric slow–wave activity was seen on electroencephalogram in each case. One patient developed marked unilateral cortical edema on MR imaging. Cerebro-spinal fluid (CSF) studies were normal for all patients. Genetic testing in each case showed a mutation of the ATP1A2 gene. One of the mutations identified is a novel mutation. Discussion: Genetic mutation of the ATP1A2 gene results in a channelopathy which is thought to predispose to spreading depolarization, the probable physiologic correlate of migraine aura. We hypothesize that widespread prolonged depolarization accounts for the characteristic electroencephalogram findings in these cases. Familial hemiplegic migraine should be considered in the differential diagnosis of an asymmetric encephalopathy, particularly when CSF and imaging studies are normal.